Tindakan Abuse Verbal dalam Perspektif Hadis - Eva Fatonah; Muhammad Alif (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This research is motivated by attention to the phenomenon of verbal violence which is increasingly common and often occurs without realizing it or is not guaranteed now. The emergence of verbal violence is very detrimental, both from the virtual world or social media and the real world by intimidating people by using harsh words. This research aims to analyze and identify Abuse Verbal Actions from a Hadith Perspective. Making fun of, criticizing, or ridiculing, giving bad titles, looking for other people's faults, and backbiting each other are abusive verbal behaviors, these actions have serious impacts such as disrupting self-confidence, mental disorders,increasing the risk of suicide, creating hostility and revenge, stress, eating and living disorders, and emotional instability. Hence, it is crucial for us to be mindful of our words, express love, and consistenly engage in constructive actions, both in the digital realm and the physical world. This imvolcus practicing prayer, cultivating patience, appreciating prayer, cultivating patience, appreaciating the diversity in human character, and maintaining a constant awareness of Allah SAW. This research uses library research with a qualitative descriptive approach so that conclusions can be drawn more comprehensively and integratively.